The Attitudes of the Education Preparation Diploma Students' Towards Cosmetic Surgery and its relations with some variables A field study in faculty of Education in Tishreen University - Sbeira , Fouad; Hassoun , Hanady; Yousof , Rania (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research discusses the Education Preparation Diploma Attitudes Students' Towards Cosmetic Surgery, and to study the effects of such attitudes according to variables (sex, marital status, work). To achieve the objectives of the research, was developed measure Towards Cosmetic Surgery prepared for this purpose, has been included (32) methods, then applied to a sample of students of (228) during the academic year 2017/2018. The present research used the descriptive analytical approach. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen Universities. Pilot sample consisted of (38) students, Reliability was established by Cronbach – Alpha Reliability (0.92(, and Spearman-Brown (0.798) by Split- half. The research ended up with the following results: - The Attitudes of the discusses the Education Preparation Diploma Students' Towards Cosmetic Surgery at educational Tishreen University was positive. - There were no significant statistical differences in attitudes the Education Preparation Diploma Students' Towards Cosmetic Surgery according to work variable. - There were significant statistical differences in attitudes the Education Preparation Diploma Students' Towards Cosmetic Surgery according to sex variable in favor of the females. - There were significant statistical differences in attitudes the Education Preparation Diploma Students' Towards Cosmetic Surgery according to marital status variable in favor of the singles. - There were effects of such attitudes according to variables (sex, marital status, work) Towards Cosmetic Surgery. The research introduced following proposals preparing programs in (schools and Universities) and mass media to lessening following any phenomenon to result psychological stresses to rush Cosmetic Surgery.